Necesidades de atención de enfermería en salud mental desde la esfera psicoafectiva de las adolescentes en gestación. Una revisión narrativa de literatura (2022)
Adolescent pregnancy has become a growing phenomenon in Colombian society, where young women experience a transformation in their bodies and a need for adaptation on a psychological level; conditions that can affect their mental health and even generate a negative impact, with outcomes such as self-harm, rejection of the newborn, among others. Taking into account the above, this project describes aspects known in the scientific literature of the needs of the psycho-affective sphere in pregnant adolescents through a narrative literature review, using the databases: PubMed, Scielo and Lilacs. Carrying out a selection process of articles that can contribute to the investigation, the due debugging was carried out through the PRISMA tool, where a total of 88 articles were obtained from the total reviewed, to then proceed to manage the main categories and/or themes, in which 3 categories of analysis are presented as a result; as well as its subcategories which are divided into Mental Health (Stress, anxiety and depression); Complications (Social deficiencies and impact on the life project) and Support network and partner (Problems with the partner, Stigmatization and abuse) in the study according to the organization by categories of analysis, there is high evidence that depression is a factor of high impact that affects the psycho-affective sphere of pregnant adolescents, generating needs in them that can be intervened by nursing to induce a more comfortable gestation process..